Mathematical, cognitive and didactic elements of the multiplicative conceptual field investigated within a Rasch assessment and measurement framework - Long, Margaret Caroline (School of Education, 2015)
How may the essential elements of a framework including mathematical, cognitive, and didactic elements, and applied in the multiplicative conceptual field, address the challenges in mathematics education, and inform the curriculum and the validity of assessment processes.